MEMETAKAN REMAH KUE MUFFIN: Studi Analisis Jaringan Sosial pada Cuitan Tentang The Muffin Song - Gemilang Bayu Ragil Saputra; Edi Santoso; Mite Setiansah; Adhi Iman Sulaiman; Nana Sutikna; Nuryanti (Kinesik, 2023)
The Muffin Song is a music video that sparked debate regarding the contents of the lyrics and visuals and how social media users used it as background music of unrelated videos. Thus, we studied the interaction between social media users, focused on Twitter, to understand, map and describe the occurred interactions between users. In this study, we used quantitative approach based on Social Network Analysis (SNA). The results showed that most users have limited interactions with other users and is separate from each other. Although, many users interacted with each other strongly in a group of users. Group to group interactions also occurred, with one or more users acted as intermediary between groups.